Mobile applications development on the google Android phone 2 - Cao, Minh Quoc Huy (2013)
Singapore currently has one of the most comprehensive bus and MRT system in the world. With this enormous system, there should be some methods for the user to quickly find how to get to his/her desired location quickly.